Job machine, think tank, or both: What makes corporate spinoffs different? - Helmut Fryges; Bettina Müller; Michaela Niefert (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
One way through which knowledge and technology transfer can take place is through the foundation of new firms by former employees of incumbent private firms. In this paper, we examine whether knowledge transferred from the incumbent causally affect employment growth and postentry innovation activities of the new firm. We focus on start-ups for which a new idea (a new product, technology, production process or management concept), which the founder developed during her work as an employee, was essential for setting up the new business. These firms are denoted corporate spinoffs. Using data from German start-ups founded in the period from 2005 to 2008, we apply nearest neighbour propensity score matching. We find that corporate spinoffs outperform other start-ups founded by former employees of incumbent private firms that are not based on an essential idea in terms of post-entry innovation activities. However, we cannot show that corporate spinoffs benefit from the transferred idea in terms of employment growth. We conclude that a transferred idea is primarily an input factor and a stimulus for subsequent post-entry innovation activities of corporate spinoffs.
urn:nbn:de:bsz:180-madoc-352477
Keywords: L26; L25; O31; C21; 330; knowledge and technology transfer; corporate spinoffs; propensity score matching; KfW/ZEW Start-Up Panel